2015
DOI: 10.1159/000368444
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Distribution of Surfactants in the Stratum Corneum by Combined ATR-FTIR and Tape-Stripping Experiments

Abstract: Combined ATR-FTIR (attenuated total reflection-Fourier transform infrared) spectroscopy and tape-stripping experiments in vitro on porcine ear skin were used to investigate the spatial distribution of different surfactants in the stratum corneum (SC). To reveal a possible connection between the size of the formed micelles and skin penetration, dynamic light-scattering measurements of the aqueous surfactant solutions were also taken. Compared to an alkyl polyglycoside and sucrose laurate, a deeper skin penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Surfactants will compete with water for above mentioned binding sites or locations, causing skin irritation, roughness, and erythema. 2,4,7 Model experiments of Zein and BSA…”
Section: Effects Of Sds On Secondary Structure Of Keratinmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfactants will compete with water for above mentioned binding sites or locations, causing skin irritation, roughness, and erythema. 2,4,7 Model experiments of Zein and BSA…”
Section: Effects Of Sds On Secondary Structure Of Keratinmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] According to the charge of their polar groups, surfactants can The destructive effect of SDS on keratin is mainly reflected by binding to keratin and causes its denaturation. [3][4][5][6][7] Because of its small molecular weight and structural features, SDS can easily penetrate SC and reach the stratum granulosum, in which it would enhance the oxidative stress of cells, induce the production of free radicals, and increase secretion of pro-inflammatory factors such as IL-1α and lead to the occurrence of skin inflammatory reactions. 8 Research has also shown that the levels of carbonylated keratin which have a negative correlation with the skin water holding capacity, 8 can be increased, and may be one of the reasons of water loss in skin after SDS entering the active epidermis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skins were disposed of 180 min (n = 4), which was the optimal time according to the previous study (10). Next, the residual enhancers were wiped carefully and completely (11). After the pretreatment, the full-thickness skins of the rats were excised from the treated sites with scissors.…”
Section: In Situ Skin Pretreatmentmentioning
confidence: 99%
“…Either in a destructive way, by segmenting the skin, for example, with adhesive tape strips or by cryo-segmentation [ 17 , 18 ], followed by a quantification step, where high-performance liquid chromatography is the most popular method [ 19 , 20 ], or with a non-invasive method, as, for example, CRS [ 4 , 21 , 22 ]. Among other optical methods, as attenuated total reflectance infrared spectroscopy [ 23 , 24 , 25 ] or fluorescence microscopy [ 26 , 27 ], CRS has the advantage of high spatial resolution and chemical sensitivity, even when used for lateral depth scanning, making it an ideal technique for skin penetration studies. In-situ measurements have the further advantage of being even less time-consuming, as there is no separate incubation step required.…”
Section: Introductionmentioning
confidence: 99%